Evaluation of Luster, Hand Feel and Comfort Properties of Modified Polyester Woven Fabrics. Issue 4 (December 2017) - Zhou, Rong; Wang, Xueli; Yu, Jianyong; Wei, Zhenzhen; Gao, Yu
This paper reports a hollow copolyester fiber modified with polyethylene glycol and sodium-5-sulfo-bis-(hydroxyethyl)-isophthalate, abbreviated as ECDP-H, which has the potential to be a replacement for cotton. The objective evaluation of luster (contrast glossiness) and Kawabata Evaluation System for Fabrics (KES-F) (four Primary Hand Parameters and the Total Hand) of ECDP-H, PET and cotton fabrics are studied in order to investigate the cotton-like appearance of the ECDP-H. The results of moisture regain and dynamic moisture absorption values obtained indicate that the hydrophilicity of the ECDP-H fabric is better than that of PET fabric. The thermo-physiological performance for three fabrics is determined using air and water vapor permeability, wicking, warm-cooling feeling, thermal resistance and vapor resistance. The results show that the ECDP-H fabric has better hand and comfort properties than cotton.